2014
DOI: 10.5946/ce.2014.47.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Complications Related to Gastric Endoscopic Submucosal Dissection and Their Managements

Abstract: Endoscopic submucosal dissection (ESD) for early gastric cancer is a well-established procedure with the advantage of resection in an en bloc fashion, regardless of the size, shape, coexisting ulcer, and location of the lesion. However, gastric ESD is a more difficult and meticulous technique, and also requires a longer procedure time, than conventional endoscopic mucosal resection. These factors naturally increase the risk of various complications. The two most common complications accompanying gastric ESD ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 29 publications
(62 reference statements)
0
45
0
1
Order By: Relevance
“…If bleeding cannot be well controlled under endoscopy, we should switch to surgical treatment or arterial embolism without hesitation. In addition, patients with massive bleeding are advised to continue intravenous infusion of large doses of PPIs to maintain a gastric pH of above 6, so as to facilitate thrombocyte aggregation, avert thrombolysis, cease hemorrhage and prevent rebleeding …”
Section: Treatment Of Bleeding After Gastric Esdmentioning
confidence: 99%
“…If bleeding cannot be well controlled under endoscopy, we should switch to surgical treatment or arterial embolism without hesitation. In addition, patients with massive bleeding are advised to continue intravenous infusion of large doses of PPIs to maintain a gastric pH of above 6, so as to facilitate thrombocyte aggregation, avert thrombolysis, cease hemorrhage and prevent rebleeding …”
Section: Treatment Of Bleeding After Gastric Esdmentioning
confidence: 99%
“…However, there are no clinical studies to support this theory. Association studies between risk of intraprocedural bleeding and the depth of submucosal dissection would be difficult to conduct, primarily because of the clinical variability among patients, other risk factors (hypertension, coagulopathy, cirrhosis, diabetes, anticoagulant use), and factors intrinsic to the lesion (size, location, submucosal invasion, and recurrence) (4,46,47) . These confounding factors are eliminated using experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we showed that an oral extension of the buried mucosa of 0.5–7.5 mm was observed in 64.3% of patients with Barrett's adenocarcinoma. In practical settings, endoscopic treatment extending more than 1 cm proximal to the endoscopic SCJ is recommended, but larger‐sized resection can cause other complications, such as bleeding and stenosis . Accordingly, the clinical significance of preoperative detection of Barrett's mucosa buried underneath endoscopically normal epithelium has increased, although it is difficult for clinically available endoscopic modalities to detect them accurately.…”
Section: Discussionmentioning
confidence: 99%